Oncologic outcomes of calcitonin-negative medullary thyroid carcinoma - Yue, Wenliang; Zhang, Yong (Frontiers in Endocrinology, 2022)
Objective: Calcitonin (Ct)-negative medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor. This study aimed to clarify its incidence, clinicopathologic characteristics, management, and treatment outcome. Methods: We retrospectively analyzed data of patients with primary MTC. Patients were divided into two groups according to the preoperative serum Ct level (Ct-negative and Ct-positive). The demographic, pathologic, and molecular characteristics, and treatment outcomes were compared between the two groups. In the Ct-negative group, we analyzed the association between the operation type and treatment outcome. Results: Of the total 312 patients, 24 were diagnosed with Ct-negative MTC. The rate of lymph node metastasis was significantly higher in the Ct-positive than in the Ct-negative group (47.9% vs. 0%, p<0.001). The proportion of patients with Ki-67 ≤10% was significantly higher in the Ct-negative than in the Ct-positive group (87.5% vs. 38.2%, p<0.001). Excellent response was achieved by 91.7% and 34.7% of patients in the Ct-negative and Ct-positive groups, respectively (p<0.001). In the Ct-negative group, excellent response was achieved by all female patients, but only 50% of male patients. Conclusions: Ct-negative MTC is rare and unlikely to develop lymph node metastasis. Unilateral lobectomy tends to provide a satisfactory chance of excellent response; however, this requires further validation.